2022
DOI: 10.1101/2022.08.22.22279095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physicians’ Attitudes towards Secondary Use of Clinical Data for Biomedical Research Purposes in Germany. Results of a Quantitative Survey

Abstract: BackgroundFor biomedical data-driven research purposes, secondary use of clinical data carries great but largely untapped potential. Physicians’ attitudes and their needs towards secondary data use are essential to inform its practical and ethically sound implementation but are currently understudied.ObjectiveTherefore, the objectives of the study are to assess physicians’ (i) general attitudes and concerns, (ii) willingness to adapt workflows and to make data available for secondary use, (iii) group-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a survey of cancer patients and physicians, 68% of physicians confirmed that they had such a professional obligation 3 , and 91% of patients expected physicians to share their patients' data for SeConts. 4 There is debate around the duty of patients to participate in (interventional) biomedical research in general 5 and specifically whether patients should share their data for SeConts.…”
Section: State Of Bioethical Researchmentioning
confidence: 99%
“…In a survey of cancer patients and physicians, 68% of physicians confirmed that they had such a professional obligation 3 , and 91% of patients expected physicians to share their patients' data for SeConts. 4 There is debate around the duty of patients to participate in (interventional) biomedical research in general 5 and specifically whether patients should share their data for SeConts.…”
Section: State Of Bioethical Researchmentioning
confidence: 99%